Pain In Patients With Multipe Sclerosis - Mussa, Khalid I.; Fayrouz Abd, Mo'taz (Journal of the Faculty of Medicine Baghdad, 2007)
Background: pain is frequently listed among initial symptoms of MS or an occurring in the course of the disease.Patients and Methods: one hundred thirty MS patients diagnosed according to Macdonald's criteria compared with 115 matched age and sex control were interviewed about pain Neuropathic, somatic and headache.Results: Neuropathic pain was significantly higher in MS than control group, while LLD and ARP were of no significance difference between two groups. For somatic pain there was significant increase in MS.Conclusion: pain is common in MS especially LLD. There is no significant difference between pain subtypes and duration of disease and FS, EDSS.